Systemically Silencing Long Non-coding RNAs Maclpil With Short Interfering RNA Nanoparticles Alleviates Experimental Ischemic Stroke by Promoting Macrophage Apoptosis and Anti-inflammatory Activation - Wang, Yan; Liu, Cuiying; Chen, Yong; Chen, Tiffany; Han, Tao; Xue, Lixiang; Xu, Baohui (Frontiers in Cardiovascular Medicine, 2022)
Background: Maclpil is a proinflammatory long noncoding RNA highly expressed on monocyte-derived macrophages in ischemic brain. This study investigated the impact and the mechanisms of systemically delivering nanoparticle Maclpil siRNA on experimental ischemic stroke in a mouse model. Methods: Ischemic stroke (focal cerebral ischemia) was induced in male C57BL/6 mice through middle cerebral artery occlusion. Three hours thereafter, mice were intravenously injected with Maclpil siRNA or scramble siRNA nanoparticles. Bone marrow cell-derived macrophages were transfected with Maclpil or scramble siRNA and subjected to oxygen glucose deprivation culture. The influence of silencing Maclpil on stroke outcomes, neuroinflammation, and macrophage fates was assessed via histology, flow cytometry, western-blotting and quantitative PCR analysis. Results: Three days following stroke induction, siRNA silencing Maclpil substantially reduced ischemic infraction size and improved neurological behaviors. Silencing Maclpil also markedly attenuated the accumulation of monocyte-derived macrophages, CD4+ T cells, and CD8+ T cells in the ischemic hemisphere without affecting microglia cellularity. Reciprocally, myeloid cells and both subsets of T cells were elevated in mouse peripheral blood following Maclpil siRNA treatment. Under oxygen glucose deprivation condition that mimicked hypoxia and hypoglycemia in vitro, Maclpil siRNA silencing augmented macrophage apoptosis in conjunction with upregulation of proapoptotic Bax and caspase 3 expression. siRNA knocking down Maclpil skewed macrophages from proinflammatory classical towards anti-inflammatory alternative activation as evidenced by increased arginase 1, Ym1, and Fizz1 and reduced inducible nitric oxide synthase, IL-1β, and TNF-α mRNA levels. Consistent with macrophage phenotype switching, silencing Maclpil by siRNA enhanced fatty acid oxidation as indicated by increased mRNA levels of 3 key metabolic enzymes (ACADM, ACADVL and HADHA). Conclusion: Systemically silencing Maclpil by siRNA nanoparticles attenuated experimental ischemic stroke by promoting macrophage apoptosis and anti-inflammatory alternative activation. Identifying and targeting Maclpil human homolog(s) may help develop novel therapy for stroke clinical management.